MIL-101(Cr) / In2S3 composite photocatalyst and preparation method and application thereof

CN122895048APending Publication Date: 2026-10-13NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611328995.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,上述复合材料体系复杂、制备步骤繁琐,且光催化活性和产氢效率仍有待进一步提高

Benefits of technology

[0022]1.本发明通过将MIL-101(Cr)与In2S3进行物理复合,构建了具有紧密异质界面的复合光催化剂。得益于二者能带结构的高度匹配,在可见光激发下,光生电子可快速从In2S3转移至MIL-101(Cr),有效抑制了光生载流子的复合,显著提高了光量子效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895048A_ABST
    Figure CN122895048A_ABST
Patent Text Reader

Abstract

The application discloses a MIL-101(Cr) / In2S3 composite photocatalyst and a preparation method and application thereof, and belongs to the technical field of composite photocatalytic materials.The composite photocatalyst is formed by physically compounding MIL-101(Cr) with an octahedral structure and In2S3 with a flower-like microsphere structure, MIL-101(Cr) is anchored on the surface and between the sheet structures of In2S3, and a heterojunction interface is formed between the two.The preparation method comprises the following steps: hydrothermally synthesizing MIL-101(Cr) and In2S3 respectively, and then stirring and compounding the two at room temperature according to a proportion.The application constructs a composite photocatalyst with a close heterojunction interface by physically compounding MIL-101(Cr) and In2S3.Benefiting from the high matching of the band structures of the two, under visible light excitation, photo-generated electrons can be quickly transferred from In2S3 to MIL-101(Cr), the recombination of photo-generated carriers is inhibited, and the photo quantum efficiency is significantly improved.The composite photocatalyst can efficiently degrade tetracycline under visible light, when the mass ratio of MIL-101(Cr) to In2S3 is 0.5:0.375, the degradation rate of tetracycline reaches 94.8% within 180 min, and the stability is excellent; and the composite photocatalyst also has good photocatalytic hydrogen production performance, and the hydrogen production amount reaches 1753.16 micromoles in 4 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite photocatalytic materials technology, specifically to a MIL-101(Cr) / In2S3 composite photocatalyst, its preparation method, and its applications in photocatalytic degradation of tetracycline and photocatalytic hydrogen production. Background Technology

[0002] Tetracycline (TC), one of the most widely used broad-spectrum antibiotics globally, is extensively applied in human medicine, livestock farming, and aquaculture. However, tetracycline is difficult to completely metabolize in humans and animals, with most of it entering the environment through excretion in its original form or as metabolites. Due to its complex molecular structure, high chemical stability, and poor biodegradability, it has become a significant emerging pollutant in aquatic ecosystems. More seriously, residual tetracycline in the environment can induce the generation and spread of resistant microorganisms and antibiotic resistance genes, posing a serious threat to public health. Therefore, developing efficient, economical, and environmentally friendly tetracycline pollution remediation technologies has become a crucial issue urgently needing to be addressed in the field of environmental science.

[0003] Among numerous water treatment technologies, photocatalysis is considered a green and sustainable approach to solving antibiotic pollution problems due to its advantages, such as being driven by solar energy, mineralizing organic pollutants at room temperature, and not producing secondary pollution. The core of photocatalysis technology lies in the development of high-performance photocatalytic materials.

[0004] In₂S₃ is an important visible-light-responsive semiconductor photocatalyst with a suitable band gap (approximately 1.8–2.3 eV), showing broad application prospects in photocatalytic degradation of organic pollutants and photocatalytic water splitting for hydrogen production. However, single In₂S₃ photocatalysts still face bottlenecks such as high recombination rates of photogenerated carriers and insufficient active sites, leading to a large number of recombinations of photogenerated electron-hole pairs. This results in a insufficient number of photogenerated electrons available to participate in interfacial reactions, limiting further improvements in its quantum efficiency.

[0005] MIL-101(Cr) is a metal-organic framework material with high specific surface area, excellent water stability, and chemical stability, attracting widespread attention in the field of photocatalysis. Studies have shown that MIL-101(Cr) exhibits good potential in photocatalytic degradation of organic pollutants and photocatalytic hydrogen production. However, the limited utilization efficiency of visible light by MIL-101(Cr) greatly restricts its application in sunlight-driven photocatalytic reactions.

[0006] To address these issues, researchers have attempted to suppress photogenerated carrier recombination and broaden the light absorption range by constructing heterojunctions. For example, existing technologies disclose a TiO2@In2S3 / MIL-101(Cr) ternary composite material, which can remove 97% of tetracycline (30 mg / L) within 210 minutes under visible light irradiation; other literature reports the use of In2S3 / polyimide Z-type heterojunctions for the photocatalytic degradation of tetracycline; and other studies have used PdS / In2S3 composite materials for photocatalytic hydrogen production. However, these composite material systems are complex, the preparation steps are cumbersome, and the photocatalytic activity and hydrogen production efficiency still need further improvement. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a MIL-101(Cr) / In2S3 composite photocatalyst, its preparation method, and its applications in photocatalytic degradation of tetracycline and photocatalytic hydrogen production.

[0008] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0009] A MIL-101(Cr) / In2S3 composite photocatalyst is formed by physical composite of MIL-101(Cr) and In2S3. The MIL-101(Cr) has an octahedral structure, and the In2S3 has a flower-like microsphere structure assembled from nanosheets. The MIL-101(Cr) is anchored on the surface and between the layers of the In2S3 sheet structure, forming a heterogeneous interface between the two.

[0010] As a further aspect of the present invention, the mass ratio of MIL-101(Cr) to In2S3 is 0.5:0.25 to 0.5.

[0011] As a further aspect of the present invention, the mass ratio of MIL-101(Cr) to In2S3 is 0.5:0.375.

[0012] A method for preparing a MIL-101(Cr) / In2S3 composite photocatalyst includes the following steps:

[0013] Step 1: Preparation of MIL-101(Cr): Dissolve chromium source and terephthalic acid in deionized water, stir and mix, then transfer to a high-pressure reactor for hydrothermal reaction. After cooling, collect the precipitate, wash and dry it to obtain MIL-101(Cr).

[0014] Step 2, Preparation of In2S3: Indium source, sulfur source and urea are dispersed in a mixed solvent of ethanol and water, stirred and mixed, and then transferred to a high-pressure reactor for hydrothermal reaction. After cooling, the precipitate is collected, washed and dried to obtain In2S3.

[0015] Step 3, Physical Combination: The MIL-101(Cr) obtained in Step 1 and the In2S3 obtained in Step 2 are mixed in a certain proportion and stirred at room temperature. After washing and drying, the MIL-101(Cr) / In2S3 composite photocatalyst is obtained.

[0016] As a further aspect of the present invention, in step one, the chromium source is Cr(NO3)3·9H2O, and the molar ratio of the chromium source to terephthalic acid is 1:1; the temperature of the hydrothermal reaction is 160-200℃, and the time is 16-24h.

[0017] As a further embodiment of the present invention, in step two, the indium source is InCl3·4H2O, the sulfur source is thioacetamide, and the molar ratio of InCl3·4H2O, thioacetamide and urea is 1:2:1.7; the hydrothermal reaction temperature is 160-200℃ and the time is 10-16h.

[0018] As a further embodiment of the present invention, in step three, the stirring and compounding time is 20 to 28 hours; the mass ratio of MIL-101(Cr) to In2S3 is 0.5:0.25 to 0.5.

[0019] This invention also provides the application of the above-mentioned MIL-101(Cr) / In2S3 composite photocatalyst in the photocatalytic degradation of tetracycline. The photocatalytic degradation conditions are as follows: tetracycline solution concentration of 10 mg / L, pH value of 3–11, composite photocatalyst dosage of 20–40 mg / 100 mL tetracycline solution, visible light with a wavelength ≥420 nm as the light source, and illumination time of 120–240 min. Preferably, the tetracycline solution concentration is 10 mg / L, pH value is 7, and the composite photocatalyst dosage is 30 mg / 100 mL tetracycline solution.

[0020] This invention also provides the application of the above-mentioned MIL-101(Cr) / In2S3 composite photocatalyst in photocatalytic hydrogen production. The conditions for photocatalytic hydrogen production are as follows: the composite photocatalyst is dispersed in an aqueous solution containing triethanolamine, and hydrogen is produced by irradiation with visible light of wavelength ≥420nm.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. This invention constructs a composite photocatalyst with a tight heterogeneous interface by physically combining MIL-101(Cr) with In2S3. Thanks to the high band structure matching between the two, photogenerated electrons can rapidly transfer from In2S3 to MIL-101(Cr) under visible light excitation, effectively suppressing recombination of photogenerated carriers and significantly improving quantum efficiency.

[0023] 2. In the composite photocatalyst of the present invention, MIL-101(Cr) is uniformly anchored on the surface and between the layers of the flower-like microsphere layered structure of In2S3, forming a tight heterogeneous interface contact between the two, which not only preserves their respective crystal structures, but also provides a channel for the rapid transfer of photogenerated charges.

[0024] 3. The composite photocatalyst of this invention significantly broadens the absorption response range of the material in the visible light region, improving the efficiency of solar energy capture and utilization; at the same time, it increases the surface adsorption active sites of tetracycline molecules, accelerating the interfacial catalytic reaction kinetics.

[0025] 4. The composite photocatalyst of this invention exhibits excellent performance in the photocatalytic degradation of tetracycline. Experiments show that under the conditions of tetracycline concentration of 10 mg / L, catalyst dosage of 30 mg / 100 mL, and pH=7, 0.375 MIS (MIL-101(Cr) to In2S3 mass ratio of 0.5:0.375) achieves a tetracycline degradation rate of 94.8% within 180 min of visible light irradiation, significantly superior to single MIL-101(Cr) (10.9%) and single In2S3 (67.8%). Degradation kinetic studies show that 0.375 MIS has the largest kinetic constant, 0.01227 min. -1 It is much larger than MIL-101(Cr) (5.85×10⁻⁶). -4 min -1 ), In2S3 (0.0048min -1 ), 0.25 MIS (0.00614 min) -1 ) and 0.5 MIS (0.00413 min) -1 After five cycles of use, the degradation rate decreased by only 5.2%, indicating that the catalyst has excellent stability.

[0026] 5. The composite photocatalyst of this invention also exhibits outstanding performance in photocatalytic hydrogen production. Experiments show that under 4 hours of visible light irradiation, the total hydrogen production of 0.375 MIS reaches 1753.16 μmol, with a single-hour hydrogen production rate as high as 438.29 μmol, far superior to single MIL-101(Cr) (19.4 μmol) and single In2S3 (441.08 μmol). After five cycles, the hydrogen production only decreases by 5.3%, demonstrating good cycle stability. Attached Figure Description

[0027] Figure 1 X-ray diffraction (XRD) patterns of MIL-101(Cr), In2S3 (and MIL-101(Cr) / In2S3 composite material).

[0028] Figure 2The images show (a) scanning electron microscope (SEM) images of MIL-101(Cr), (b) SEM images of In2S3, and (c) and (d) SEM images of the MIL-101(Cr) / In2S3 composite material.

[0029] Figure 3 (a) Degradation curves of tetracycline by different catalysts, (b) First-order degradation kinetics curves, (c) Bar chart of kinetic constants, and (d) Cyclic degradation curves at 0.375 MIS.

[0030] Figure 4 (a) Degradation curves of tetracycline by 0.375 MIS under different pH conditions, (b) First-order degradation kinetic curves, and (c) Bar chart of kinetic constants.

[0031] Figure 5 (a) Line graph of hydrogen production for different catalysts, (b) Bar graph of hydrogen production efficiency for different catalysts, and (c) Cyclic hydrogen production curve at 0.375 MIS. Detailed Implementation

[0032] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.

[0033] Example 1: Preparation of MIL-101(Cr)

[0034] 4 mmol of Cr(NO3)3·9H2O and 4 mmol of terephthalic acid (H2BDC) were dissolved in 60 mL of deionized water and stirred continuously for 30 min. The resulting solution was then transferred to a 100 mL autoclave lined with polytetrafluoroethylene and heated at 180 °C for 20 h. After cooling to room temperature, the gray-green precipitate was collected by centrifugation. The resulting gray-green powder was washed three times by reflux with DMF and ethanol, and then dried at 70 °C for 12 h to obtain MIL-101(Cr).

[0035] Example 2: Preparation of In2S3

[0036] 1.0 mmol InCl3·4H2O, 2.0 mmol thioacetamide (TAA), and 1.7 mmol urea (CO(NH2)2) were dispersed in a 50 mL solution of ethanol and water in a 1:1 volume ratio. After stirring at room temperature for 1 h, the solution was transferred to a 100 mL autoclave lined with polytetrafluoroethylene and reacted at 180 °C for 12 h. After naturally cooling to room temperature, the mixture was washed three times with deionized water and ethanol, centrifuged to obtain a dark yellow powder, and then dried at 60 °C for 12 h to obtain In2S3.

[0037] Example 3: Preparation of MIL-101(Cr) / In2S3 composite photocatalyst

[0038] 0.5 g of MIL-101(Cr) prepared in Example 1 was mixed with x g of In2S3 (x = 0.25, 0.375, 0.5) and stirred continuously at room temperature for 24 h. After centrifugation, the mixture was washed three times with ethanol and dried at 60 °C for 12 h to obtain a brown powder. The samples were named 0.25 MIS, 0.375 MIS, and 0.5 MIS according to the different masses of In2S3 added.

[0039] Example 4: Structural and morphological characterization of the MIL-101(Cr) / In2S3 composite photocatalyst

[0040] The crystal structure of materials is analyzed by X-ray diffraction (XRD). Figure 1 The results showed that the characteristic diffraction peaks of In2S3 were mainly located at 28.80°, 33.44°, and 47.99°, corresponding to the (111), (200), and (220) crystal planes of In2S3, respectively (PDF#05-0731). The XRD results of MIL-101(Cr) were consistent with those reported in previous literature. The XRD patterns of the composite materials both showed the main diffraction peaks of MIL-101(Cr) and In2S3, indicating that both maintained their original crystal structures during the composite process, and the composite was successfully achieved.

[0041] Material morphology was analyzed using scanning electron microscopy (SEM). Figure 2 (a) shows that MIL-101(Cr) exhibits a regular octahedral structure with a smooth surface, good dispersibility, and uniform size distribution. Figure 2 (b) shows that In2S3 exhibits a flower-like microsphere structure assembled from thin nanosheets. Figure 2 (c) and Figure 2 (d) shows that MIL-101(Cr) is uniformly anchored in the lamellar structure and on the outer surface of In2S3. The structure of MIL-101(Cr) is not destroyed during the composite process, and a tight heterogeneous interface is formed between the two.

[0042] Example 5: Performance testing of MIL-101(Cr) / In2S3 composite photocatalyst for tetracycline degradation

[0043] A 300W xenon lamp with a cutoff filter (λ≥420nm) was used as the visible light source. A 10mg / L tetracycline solution with pH=7 was prepared to simulate antibiotic wastewater. 100mL of the simulated wastewater was added to a 200mL reactor. Under room temperature conditions, 30mg of photocatalyst was added, and the solution was stirred for 60min in the dark to reach adsorption equilibrium. Then, the photocatalytic reaction was carried out for 3h under a 300W xenon lamp (with a 420nm cutoff filter), with samples taken every 30min. The concentration of residual tetracycline in the filtered solution (sample filtered using a 0.45μm syringe filter) was analyzed using a UV-Vis spectrophotometer (λ=357nm).

[0044] The degradation rate of tetracycline is calculated using the following formula:

[0045]

[0046] Where C0 is the initial concentration of tetracycline, and C_t is the concentration of tetracycline after degradation.

[0047] Figure 3 (a) The results showed that after 60 min of adsorption equilibrium, 0.375 MIS exhibited the best adsorption performance. After 180 min of visible light irradiation, the degradation rates of tetracycline by MIL-101(Cr), In2S3, 0.25 MIS, 0.375 MIS, and 0.5 MIS were 10.9%, 67.8%, 81.2%, 94.8%, and 69.9%, respectively, with 0.375 MIS showing the best photocatalytic degradation effect.

[0048] Degradation kinetics studies have shown that ( Figure 3 (b) and Figure 3 (c) The kinetic constants of the composite catalysts were all greater than those of the two monomers. The 0.375 MIS catalyst had the largest kinetic constant, at 0.01227 min. -1 The other catalysts were MIL-101(Cr) (5.85 × 10⁻⁶). -4 min -1 ), In2S3 (0.0048min -1 ), 0.25 MIS (0.00614 min) -1 ) and 0.5 MIS (0.00413 min) -1 ).

[0049] Cyclic stability test ( Figure 3 (d) shows that after five cycles, the degradation rate of 0.375MIS decreased by only 5.2%, indicating that the composite material has excellent stability.

[0050] Example 6: Effect of pH on the degradation of tetracycline by 0.375 MIS

[0051] Add 30 mg of 0.375 MIS catalyst to 100 mL of 10 mg / L tetracycline solution and adjust the pH to 3, 5, 7, 9 and 11 respectively. Figure 4 (a) The results showed that the degradation efficiencies under different pH conditions were 54.3%, 83.9%, 94.8%, 91.9% and 84.2%, respectively, with the highest degradation rate of 94.8% at pH=7.

[0052] Dynamics study ( Figure 4 (b) and Figure 4 (c) indicates that the degradation of the composite material at different pH values ​​follows a first-order kinetic curve, with the largest kinetic constant (k = 0.01227 min) at pH = 7. -1 The kinetic constants at other pH values ​​were pH=3 (0.00292 min). -1 pH=5 (0.00797 min) -1 pH=9 (0.01092 min) -1 ) and pH=11 (0.00826 min) -1 ).

[0053] Example 7: Photocatalytic hydrogen production performance test of MIL-101(Cr) / In2S3 composite photocatalyst

[0054] Photocatalytic hydrogen production was measured using a gas-tight recirculation system (CEL-PAEM-D8, Beijing Zhongjiao Jinyuan Technology Co., Ltd.). First, the system was evacuated with high-purity nitrogen to remove residual air. A 300W xenon lamp was used as the light source, and the reaction temperature was maintained at 5°C through cooling water circulation. 10 mg of photocatalyst was dispersed in 100 mL of an aqueous solution containing 10% triethanolamine (TEOA). The hydrogen production was continuously monitored for 4 hours using an online gas chromatograph (GC7920), measured every 60 minutes.

[0055] Figure 5 (a) The results showed that the hydrogen production of MIL-101(Cr) and In2S3 under 4h illumination was 19.4 μmol and 441.08 μmol, respectively. After constructing the heterojunction, the hydrogen production of all composite samples increased significantly, with 0.375 MIS having the highest hydrogen production at 1753.16 μmol, which was significantly better than 0.25 MIS and 0.5 MIS. Figure 5 (b) shows that the single-hour hydrogen production rate of 0.375 MIS is as high as 438.29 μmol.

[0056] Cyclic stability test ( Figure 5 (c) shows that hydrogen production decreased by only 5.3% after five cycles, indicating that 0.375MIS has excellent cycle stability.

[0057] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A MIL-101(Cr) / In2S3 composite photocatalyst, characterized in that, The composite photocatalyst is formed by physical composite of MIL-101(Cr) and In2S3. MIL-101(Cr) has an octahedral structure, and In2S3 has a flower-like microsphere structure assembled from nanosheets. MIL-101(Cr) is anchored on the surface and between the layers of the In2S3 sheet structure, forming a heterogeneous interface between the two.

2. The MIL-101(Cr) / In2S3 composite photocatalyst according to claim 1, characterized in that, The mass ratio of MIL-101(Cr) to In2S3 is 0.5:0.25 to 0.

5.

3. The MIL-101(Cr) / In2S3 composite photocatalyst according to claim 2, characterized in that, The mass ratio of MIL-101(Cr) to In2S3 is 0.5:0.

375.

4. A method for preparing the MIL-101(Cr) / In2S3 composite photocatalyst as described in any one of claims 1 to 3, characterized in that, Includes the following steps: Step 1: Preparation of MIL-101(Cr): Dissolve chromium source and terephthalic acid in deionized water, stir and mix, then transfer to a high-pressure reactor for hydrothermal reaction. After cooling, collect the precipitate, wash and dry it to obtain MIL-101(Cr). Step 2, Preparation of In2S3: Indium source, sulfur source and urea are dispersed in a mixed solvent of ethanol and water, stirred and mixed, and then transferred to a high-pressure reactor for hydrothermal reaction. After cooling, the precipitate is collected, washed and dried to obtain In2S3. Step 3, Physical Combination: The MIL-101(Cr) obtained in Step 1 and the In2S3 obtained in Step 2 are mixed in a certain proportion and stirred at room temperature. After washing and drying, the MIL-101(Cr) / In2S3 composite photocatalyst is obtained.

5. The preparation method of the MIL-101(Cr) / In2S3 composite photocatalyst according to claim 4, characterized in that, In step one, the chromium source is Cr(NO3)3·9H2O, and the molar ratio of the chromium source to terephthalic acid is 1:1; the hydrothermal reaction temperature is 160-200℃, and the time is 16-24h.

6. The preparation method of the MIL-101(Cr) / In2S3 composite photocatalyst according to claim 4, characterized in that, In step two, the indium source is InCl3·4H2O, the sulfur source is thioacetamide, and the molar ratio of InCl3·4H2O, thioacetamide and urea is 1:2:1.7; the hydrothermal reaction temperature is 160-200℃ and the time is 10-16h.

7. The preparation method of the MIL-101(Cr) / In2S3 composite photocatalyst according to claim 4, characterized in that, In step three, the stirring and compounding time is 20 to 28 hours; the mass ratio of MIL-101(Cr) to In2S3 is 0.5:0.25 to 0.

5.

8. The application of the MIL-101(Cr) / In2S3 composite photocatalyst as described in any one of claims 1 to 3 in the photocatalytic degradation of tetracycline and / or photocatalytic hydrogen production.

9. The application according to claim 8, characterized in that, The conditions for photocatalytic degradation of tetracycline are as follows: the concentration of the tetracycline solution is 10 mg / L, the pH value is 3-11, the amount of composite photocatalyst is 20-40 mg / 100 mL of tetracycline solution, and visible light with a wavelength ≥420 nm is used as the light source.

10. The application according to claim 8, characterized in that, The conditions for photocatalytic hydrogen production are as follows: the composite photocatalyst is dispersed in an aqueous solution containing triethanolamine, and hydrogen is produced by irradiation with visible light of wavelength ≥420nm.